2001
DOI: 10.1207/s15324826an0801_6
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Assessment of Neuropsychological Functioning, Psychiatric Status, Functional Disability and Employment Status in Chronic Fatigue Syndrome

Abstract: The longitudinal course of subjective and objective neuropsychological functioning, psychological functioning, disability level, and employment status in chronic fatigue syndrome (CFS) was examined. The relations among several key outcomes at follow-up, as well as the baseline characteristics that predict change (e.g., improvement), were also evaluated. The study sample consisted of 35 individuals who met the 1988 and 1994 CFS case definition criteria of the Centers for Disease Control (CDC) at intake. Partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
54
2
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 26 publications
8
54
2
2
Order By: Relevance
“…In clinical practice, most patients report a progressive worsening in their cognitive functioning over time which would appear to indicate that cognitive impairment is directly associated with CFS. However, empirical research does not confirm this hypothesis (Cope, Pernet, Kendall, & David, 1995;Tiersky, et al, 2001). In a recent study carried out by our team, we also conclude that there is no progressive cognitive dysfunction in patients with CFS (Santamarina-Perez, .…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…In clinical practice, most patients report a progressive worsening in their cognitive functioning over time which would appear to indicate that cognitive impairment is directly associated with CFS. However, empirical research does not confirm this hypothesis (Cope, Pernet, Kendall, & David, 1995;Tiersky, et al, 2001). In a recent study carried out by our team, we also conclude that there is no progressive cognitive dysfunction in patients with CFS (Santamarina-Perez, .…”
Section: Introductionmentioning
confidence: 55%
“…Since depressive symptoms and anxiety are frequently observed in patients with CFS (Harvey, Wessely, Kuh, & Hotopf, 2009), the possibility that these may contribute to impaired cognitive performance must be considered. Some studies have found a relationship between cognitive deficits and depression and anxiety in CFS (Michiels & Cluydts, 2001;Tiersky et al, 2001). However, the majority of neuropsychological studies that have examined this relationship conclude that cognitive dysfunction in CFS is not a function of depression or anxiety (Busichio, et al, 2004;Short, et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, there is not any practice effect, because it is a cross-sectional study, with only one examination. Tiersky et al (2001), included measures of attention (PASAT, forward and backward digit) and memory (CVLT and ROCFT), but this study didn´t incorporate other cognitive tests in which patients' performance is impaired such as Stroop reaction time, AVLT and motor Functioning (Cockshell & Mathias, 2010). So, to study how the length of the illness affects cognitive impairment in CFS patients, we should include a neuropsychological battery with measures that have been shown to be altered in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Kvinner er generelt alvorligere rammet enn menn (63) . Høy alder, flere kroniske sykdommer, og psykiatriske tilleggsdiagnoser er risikofaktorer for et alvorligere sykdomsforløp (64,65) . Pågående uheldig stress vil vaere forbundet med lengre sykdomsforløp (66) .…”
Section: Forløpunclassified
“…Prognosen er bedre for barn og unge enn for voksne uansett alvorlighetsgrad (65,67) . En meta-analyse av forløpsstudier, viste at 54-94 % av barna med CFS/ME ble friske i løpet av oppfølgingsperioden (64) .…”
Section: Forløpunclassified